Handbook on the rule of law - Rule (Edward Elgar Publishing, 2018)
"In the last half century, the rule of law has increasingly been appealed to as a common global value. The Handbook on the Rule of Law analyses the appeal of this idea, its context and background through a range of questions about the character, history and global reach of the rule of law, offering readers a definitive understanding of this central global norm. Original contributions from leading academics explore the rule of law conceptually and historically through its associated institutions, as well as examining detailed cases evaluating how the everyday application of the rule of law impacts society as a whole. Exploring a wide range of research on the social, political and economic dimensions of the rule of law, this Handbook clearly illustrates the link between the rule of law and the global political system. This informative Handbook will be key reading for postgraduate students of international relations, global politics and law, as well as for legal scholars wanting to build upon their knowledge with a wider account of the rule of law. Rese